2015
DOI: 10.1158/0008-5472.can-15-0423
|View full text |Cite
|
Sign up to set email alerts
|

WDR5 Supports an N-Myc Transcriptional Complex That Drives a Protumorigenic Gene Expression Signature in Neuroblastoma

Abstract: MYCN gene amplification in neuroblastoma drives a gene expression program that correlates strongly with aggressive disease. Mechanistically, trimethylation of histone H3 lysine 4 (H3K4) at target gene promoters is a strict prerequisite for this transcriptional program to be enacted. WDR5 is a histone H3K4 presenter that has been found to have an essential role in H3K4 trimethylation. For this reason, in this study, we investigated the relationship between WDR5-mediated H3K4 trimethylation and N-Myc transcripti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
97
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 47 publications
4
97
0
Order By: Relevance
“…The analysis of the chromatin-bound fraction also highlighted a reduction in c-Myc as a consequence of WDR5 silencing. The recent exciting finding of a direct interaction between WDR5 and c-Myc could imply that WDR5 may be recruited to chromatin to execute on Myc-dependent functions in replication (Thomas et al, 2015;Sun et al, 2015). By performing immunoprecipitation experiments for exogenously expressed Flag-WDR5 or endogenous c-Myc we confirmed the physical interaction of these two proteins in PDAC cells ( Figure 6F).…”
Section: Wdr5 Complex Protects Pdac Cells From Replicative Stress Andsupporting
confidence: 53%
“…The analysis of the chromatin-bound fraction also highlighted a reduction in c-Myc as a consequence of WDR5 silencing. The recent exciting finding of a direct interaction between WDR5 and c-Myc could imply that WDR5 may be recruited to chromatin to execute on Myc-dependent functions in replication (Thomas et al, 2015;Sun et al, 2015). By performing immunoprecipitation experiments for exogenously expressed Flag-WDR5 or endogenous c-Myc we confirmed the physical interaction of these two proteins in PDAC cells ( Figure 6F).…”
Section: Wdr5 Complex Protects Pdac Cells From Replicative Stress Andsupporting
confidence: 53%
“…On the other hand, genetic mutations of the core subunits are rarely found in human cancers. Instead, the DPY30 (51), ASH2L (24,52), and WDR5 (25,53,54) core subunits have been found to be overexpressed in cancers, show correlation of high expression levels with poor prognosis, and, in some cases, functionally promote tumorigenesis. Such differential regulations and roles elicit interesting questions relating to the exact roles of these subunits and the associated H3K4 methylation in cancer and merit further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that WDR5 drives the expression of protumorigenic gene-MDM2 with c-MYC in neuroblastoma [35]; WDR5 high expression promotes proliferation, self-renewal and chemoresistance in bladder cancer via mediating H3K4 trimethylation on cell cycle genes such as CCNA, CCNB1, CCND1, CCNE1 etc. [36]; Also it has reports that blocking of MLL-WDR5 interaction and MLL1 knockdown induced the suppression of c-MYC and BCL-2 in leukemia cells [27]; and loss of WDR5 increases expression of G-CSF, ccl9, etc., and restores granulocytic differentiation potential in C/EBPa p30-expressing AML cells [32].…”
Section: Discussionmentioning
confidence: 99%